The writers directory 1988-90 (St. James Press, 1988)
The Writers Directory 1988-90 - the completely revised and expanded eighth edition of this biennial reference work - lists more than 16,000 living writers in English from Australia, Canada, Ireland, New Zealand, South Africa, the United Kingdom and the United States, as well as writers in English from other countries. The main, directory section of the book lists fiction and nonfiction writers, poets, dramatists, and other who have written and had published at least one full-length book in English. To ensure accuracy, the editors have based entries, whenever possible, on the information provided by the entrants themselves. Each entry contains : the writer's name; pseudonyms if any ; citizenship and year of birth; brief summary of nature of writing; major current and past appointments; a detailed bibliography; and address. Additionally, a unique "yellow pages" section lists writers under their various writing categories. This section is especially useful to students, bibliographies and others who need a list of writers on a particular subject.